An ethnographic study on the impact of a novel telemedicine-based support system in the operating room. (19th August 2022) - Abraham, Joanna; Meng, Alicia; Montes de Oca, Arianna; Politi, Mary; Wildes, Troy; Gregory, Stephen; Henrichs, Bernadette; Kannampallil, Thomas; Avidan, Michael S
Abstract: Objective: The Anesthesiology Control Tower (ACT) for operating rooms (ORs) remotely assesses the progress of surgeries and provides real-time perioperative risk alerts, communicating risk mitigation recommendations to bedside clinicians. We aim to identify and map ACT-OR nonroutine events (NREs)—risk-inducing or risk-mitigating workflow deviations—and ascertain ACT's impact on clinical workflow and patient safety. Materials and Methods: We used ethnographic methods including shadowing ACT and OR clinicians during 83 surgeries, artifact collection, chart reviews for decision alerts sent to the OR, and 10 clinician interviews. We used hybrid thematic analysis informed by a human-factors systems-oriented approach to assess ACT's role and impact on safety, conducting content analysis to assess NREs. Results: Across 83 cases, 469 risk alerts were triggered, and the ACT sent 280 care recommendations to the OR. 135 NREs were observed. Critical factors facilitating ACT's role in supporting patient safety included providing backup support and offering a fresh-eye perspective on OR decisions. Factors impeding ACT included message timing and ACT and OR clinician cognitive lapses. Suggestions for improvement included tailoring ACT message content (structure, timing, presentation) and incorporating predictive analytics for advanced planning. Discussion: ACT served as a safety net with remote surveillance features and as a learning healthcare system with feedback/auditing features. Supporting strategies include adaptive coordination and harnessing clinician/patient support to improve ACT's sustainability. Study insights inform future intraoperative telemedicine design considerations to mitigate safety risks. Conclusion: Incorporating similar remote technology enhancement into routine perioperative care could markedly improve safety and quality for millions of surgical patients.